Application of "CERDIK" Behavior Model in Schools as an Effort to Improve Diabetes Mellitus Prevention Behavior: Penerapan Model Perilaku “CERDIK” di Sekolah Sebagai Upaya Peningkatan Perilaku Pencegahan Diabetes Melitus - Hariawan, Hamdan; Tidore, Martini; Rahakbauw, Greeny Z (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The prevalence of non-communicable diseases such as diabetes mellitus continues to increase every year. Teenagers today cannot be separated from unhealthy lifestyles such as smoking, eating fast food, online gaming, and lack of physical activity. The data obtained that 60 to 80 smoker students in Ambon State Aliyah Madrasah which is the work area of ​​the Air Besar Health Center. In the Air Besar Health Center in the past year, there were 207 diabetes mellitus sufferers. The expected outcome and outcome of this Community Service is increasing students' knowledge and skills towards diabetes mellitus with CERDIK behavior in schools. The service method is carried out through education and training through demonstrations. Demonstrations were given related to CERDIK behavior such as how to prevent smoking, how to manage stress, and how to read food packaging labels to reduce sugar consumption. So the results and outcomes obtained are increased knowledge and skills of students as participants of CERDIK behavior in schools. The series of community service activities can be carried out properly according to the plan. And it is expected that the person in charge of the UKS will provide other students with the CERDIK module in the school that has been given and the involvement of the Health Center is running the Non-Communicable Disease program in schools as a continuation of community service.